Anti-α-synuclein immunotherapy reduces α-synuclein propagation in the axon and degeneration in a combined viral vector and transgenic model of synucleinopathy - Spencer, Brian (Acta Neuropathol Commun, 2017)
Neurodegenerative disorders such as Parkinson’s Disease (PD), PD dementia (PDD) and Dementia with Lewy bodies (DLB) are characterized by progressive accumulation of α-synuclein (α-syn) in neurons. Recent studies have proposed that neuron-to-neuron propagation of α-syn plays a role in the pathogenesis of these disorders. We have previously shown that antibodies against the C-terminus of α-syn reduce the intra-neuronal accumulation of α-syn and related deficits in transgenic models of synucleinopathy, probably by abrogating the axonal transport and accumulation of α-syn in in vivo models. Here, we assessed the effect of passive immunization against α-syn in a new mouse model of axonal transport and accumulation of α-syn. For these purpose, non-transgenic, α-syn knock-out and mThy1-α-syn tg (line 61) mice received unilateral intra-cerebral injections with a lentiviral (LV)-α-syn vector construct followed by systemic administration of the monoclonal antibody 1H7 (recognizes amino acids 91-99) or control IgG for 3 months. Cerebral α-syn accumulation and axonopathy was assessed by immunohistochemistry and effects on behavior were assessed by Morris water maze. Unilateral LV-α-syn injection resulted in axonal propagation of α-syn in the contra-lateral site with subsequent behavioral deficits and axonal degeneration. Passive immunization with 1H7 antibody reduced the axonal accumulation of α-syn in the contra-lateral side and ameliorated the behavioral deficits. Together this study supports the notion that immunotherapy might improve the deficits in models of synucleinopathy by reducing the axonal propagation and accumulation of α-syn. This represents a potential new mode of action through which α-syn immunization might work.